A supplemental receiver coil recovers frontal and subcortical functional magnetic resonance imaging signals under half-volume head coil configuration - Yuan, Yucong; Tanaka, Toshiko; Nishiyama, Daisuke; Shimada, Yasuhiro; Fujimoto, Ichiro; Haji, Tomoki; Wada, Atsushi; Haruno, Masahiko (Neuroscience research, 2025)
The need for multisensory devices such as virtual reality and touch during functional magnetic resonance imaging (fMRI) is increasing. However, implementation of those devices requires a large presentation system, and the face-covering receiver coil obstructs their placement. To create more space, it has been proposed to remove the front half coil and place a small elliptical flex receiver coil on the participant's forehead. However, this coil configuration's signal intensity has not been evaluated quantitatively and needs validation for use in various fMRI experiments. In this study, we first compared signal-to-noise ratios of resting-state fMRI for different brain regions under full, posterior half only, and posterior half + flex coil conditions and found that the flex coil improved the fMRI signal in both frontal and subcortical regions significantly. Furthermore, we tested the flex coil during a facial expression discrimination task, finding it enabled the detection of task-related fMRI signals in areas related to emotional decision-making and perception such as the amygdala. Thus, this study demonstrated the usefulness of the flex configuration in various fMRI experiments requiring additional equipment in front of the face, expanding the range of fMRI studies. •Adding forehead coil to half-head coil recovered frontal and subcortical MR signals.•Whole brain resting-fMRI signals were quantitatively evaluated using our setup.•Task-fMRI identified significant BOLD responses in front-subcortical network.•The new coil setup enabled both forehead clearance and high-sensitivity fMRI.